Characterization of a Mycobacterium smegmatis uvrA mutant impaired in dormancy induced by hypoxia and low carbon concentration - Cordone, Angela (BioMed Central, 2011)
BACKGROUND: The aerobic fast-growing Mycobacterium smegmatis, like its slow-growing pathogenic counterpart Mycobacterium tuberculosis, has the ability to adapt to microaerobiosis by shifting from growth to a non-proliferating or dormant state. The molecular mechanism of dormancy is not fully understood and various hypotheses have been formulated to explain it. In this work, we open new insight in the knowledge of M. smegmatis dormancy, by identifying and characterizing genes involved in this behavior. RESULTS: In a library generated by transposon mutagenesis, we searched for M. smegmatis mutants unable to survive a coincident condition of hypoxia and low carbon content, two stress factors supposedly encountered in the host and inducing dormancy in tubercle bacilli. Two mutants were identified that mapped in the uvrA gene, coding for an essential component of the Nucleotide Excision Repair system (NER). The two mutants showed identical phenotypes, although the respective transposon insertions hit different regions of the uvrA gene. The restoration of the uvrA activity in M. smegmatis by complementation with the uvrA gene of M. tuberculosis, confirmed that i) uvrA inactivation was indeed responsible for the inability of M. smegmatis cells to enter or exit dormancy and, therefore, survive hypoxia and presence of low carbon and ii) showed that the respective uvrA genes of M. tuberculosis and M. smegmatis are true orthologs. The rate of survival of wild type, uvrA mutant and complemented strains under conditions of oxidative stress and UV irradiation was determined qualitatively and quantitatively. CONCLUSIONS: Taken together our results confirm that the mycobacterial NER system is involved in adaptation to various stress conditions and suggest that cells with a compromised DNA repair system have an impaired dormancy behavior.